Η ΑΞΙΟΠΟΙΗΣΗ ΤΟΥ ΜΟΝΤΕΛΟΥ ΤΗΣ ΑΝΕΣΤΡΑΜΜΕΝΗΣ ΤΑΞΗΣ ΓΙΑ ΤΟ ΘΕΑΤΡΟ/ΔΡΑΜΑ ΣΤΗΝ ΕΚΠΑΙΔΕΥΣΗ [THE USE OF THE FLIPPED CLASSROOM MODEL FOR THEATRE/DRAMA IN EDUCATION] - Zakopoulos, Vassilis (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
The flexibility of digital technologies has led to the emergence of many new educational approaches. The use and integration of digital technologies in theatre/drama education have also created new needs and perspectives, both in educational design and methodological approaches. One of these innovative methodologies is the ’flipped classroom’ model, which is based on blended learning and is applied internationally. In flipped learning, traditional classroom lectures are replaced by online programmes or educational videos, which students are asked to watch and understand at home. One of the advantages of the model is that it provides more opportunities for students to develop higher levels of thinking, as it frees up class time and provides opportunities for participation, interaction and active learning. However, the challenges for teachers are many, as they must create high quality materials, monitor their students’ progress and ensure that they are prepared for the activities that will follow in the classroom. The present study attempts to explore the existence of research efforts on the application of the flipped classroom model in the field of theatre/drama education and to weigh up the prospects and potential of its application for theatre/drama in education as a different, innovative methodological approach.